PSVII-5 Nutritional programming of prenatal beef heifer development and postnatal performance. (7th December 2018) - Long, J; Sawyer, J; Wickersham, T; Long, C; Trubenbach, L; Satterfield, M
Abstract: Nutritional insults during gestation are known to impact postnatal life, evident through altered growth and performance, and metabolic, immune, and reproductive dysfunction. In a previous study, we observed reduced pancreas weights and lower insulin concentrations in fetuses originating from dams nutrient restricted during late gestation. The present study investigated the effects of late gestation maternal nutrient restriction on postnatal growth of beef heifers. Embryos were produced in vitro utilizing Angus-type oocytes and sexed semen from one Angus sire for X-bearing sperm. Resulting embryos were transferred into virgin dams similar in age, body condition and frame score. Pregnant dams were moved into individual rationing facilities on gestation day (GD) 130 for 28-d acclimation and were randomly assigned to dietary treatments beginning on GD 158, receiving either 70% nutrient requirements (n=9; restricted) or 100% nutrient requirements (n=9; control). Individual feed intakes were adjusted twice monthly based on predicted pregnancy requirements using mean metabolic body weight. Dam BWs were recorded twice monthly, and rib eye area (REA) and last rib back fat (LRBF) were recorded monthly. Maternal BW (P0.01) and REA (PP=0.15). At calving, all dams were maintained on high-quality improved pasture to meet nutritional demands for lactation. Restricted calves were lighter than control calves (P0.05) at birth, postnatal day (PND) 35 (P0.01) and PND 70 (P=0.05). There was no difference (P>0.11) in calf BW at PND 105, 140, 175, 210, 245, 315, 350, 385, 420, or 455. At weaning (PND210) there was no difference in calf REA (P=0.45) or LRBF (P=0.39). These data support previous observations of reduced birth weight followed by compensatory growth in nutritionally restricted calves. Ongoing analyses will determine respective age at attainment of puberty and organ and carcass characteristics.